The role of human milk nutrients in preventing necrotizing enterocolitis - Sami, Ahmad S.; Frazer, Lauren C.; Miller, Claire M.; Singh, Dhirendra K.; Clodfelter, Lynda G.; Orgel, Kelly A.; Good, Misty (Frontiers in Pediatrics, 2023)
Necrotizing enterocolitis (NEC) is an intestinal disease that primarily impacts preterm infants. The pathophysiology of NEC involves a complex interplay of factors that result in a deleterious immune response, injury to the intestinal mucosa, and in its most severe form, irreversible intestinal necrosis. Treatments for NEC remain limited, but one of the most effective preventative strategies for NEC is the provision of breast milk feeds. In this review, we discuss mechanisms by which bioactive nutrients in breast milk impact neonatal intestinal physiology and the development of NEC. We also review experimental models of NEC that have been used to study the role of breast milk components in disease pathophysiology. These models are necessary to accelerate mechanistic research and improve outcomes for neonates with NEC.